Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00167-012-2151-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between femoroacetabular contact areas and hip position in the normal joint: an in vitro evaluation

Abstract: The results confirm the ability of the Hyperextension-External Rotation tests to particularly analyse the posterior region of the acetabulum. Placing the hip in 90° of Flexion-Adduction-Internal Rotation allows for testing a wider zone of the acetabulum and is not specific to abutment of the femoral head-neck region against the anterolateral acetabulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Provocative tests commonly are used to identify pathology but may have the potential to screen for injury risk factors. The FADIR often is performed to assist in diagnosing hip joint pathology, because this test position stresses a large portion of the acetabulum [15] and labrum [16]. The FADIR has high sensitivity for detecting pain and hip joint pathology in symptomatic individuals [14,17] but low specificity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Provocative tests commonly are used to identify pathology but may have the potential to screen for injury risk factors. The FADIR often is performed to assist in diagnosing hip joint pathology, because this test position stresses a large portion of the acetabulum [15] and labrum [16]. The FADIR has high sensitivity for detecting pain and hip joint pathology in symptomatic individuals [14,17] but low specificity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“… 25 , 95 A cadaveric study of hips without osseous FAI examined the effects of dancer- or gymnast-like flexibility and found that extremes of hyperextension and external rotation could generate femoroacetabular contact at the posterior-superior acetabulum. 83 …”
Section: Impingementmentioning
confidence: 99%
“…In the past 10 years, many research labs have developed new methods to study hip joint biomechanics including: digital image correlation ( Dickinson et al, 2012 , Dickinson et al, 2011 ), roentgen stereophotogrammetric analysis ( Dy et al, 2008 , Myers et al, 2011 ), digital variable resistance transducers ( Safran et al, 2011 , Smith et al, 2011 ), real-time contact-pressure measurement ( Lee et al, 2015 , Rudert et al, 2014 ), fluid infusion devices ( Cadet et al, 2012 , Dwyer et al, 2014 ), optical tracking motion analysis ( Lopomo et al, 2010 , Signorelli et al, 2013 ), 3D digital reconstructions combining CT scans and motion tracking ( Dwyer et al, 2014 , Incavo et al, 2011 ), combined use of in-vitro and finite element modelling ( Anderson et al, 2008 , Dickinson et al, 2011 , Elkins et al, 2011 ), custom built rigs in servo-hydraulic actuators/materials testing machines ( Dickinson et al, 2012 , Elkins et al, 2011 , Ito et al, 2009 , Song et al, 2012 , van Arkel et al, 2015a , van Arkel et al, 2015b ) and six-degrees-of-freedom robotic load/torque actuators ( Colbrunn et al, 2013 , Smith et al, 2014 ). Such variation in testing methodology not only allows new hypotheses to be tested but also prevents systematic bias that could result from using the same methodology with the same limitations.…”
Section: Introductionmentioning
confidence: 99%